Evaluation of the protective effect of inactivated foot and mouth disease subtype A-IRAN-05 using an electron beam in a guinea pig model - F. Motamedi Sedeh; M. Behgar; S.M. Moosavi (مجله علوم و فنون هسته‌ای, 2023)
Foot and Mouth Disease Virus (FMDV) can cause a lot of economic losses in livestock. In this research FMDV subtype A-IRAN-05 was used. FMDV was multiplied on BHK21 cells and irradiated by electron beam (10, 20, 25, 30, 35, 40, 45, 50 kGy), then the dose/response curve was drawn by Origin software. D10 value and optimum dose for virus inactivation according to the dose/ response curve and the results of the safety test and Complement Fixation test for the evaluation of antigenic characteristics were obtained at 8.33 and 55 kGy, respectively. Then irradiated vaccine and conventional vaccine were formulated with Aluminum Hydroxide gel and Saponin and used for injection on the guinea pig. The neutralizing antibody titration and splenic lymphocyte proliferation assay were shown a significant increase in humeral and cellular immunity induction in the irradiated vaccine and conventional vaccine to the negative control group (P<0.05). Also, the protective doses of irradiated and conventional vaccines were obtained at 6.28 and 6.13, respectively. It indicated the protective effect of both of the vaccines on a guinea pig.